A predictive score for atrial fibrillation in poststroke patients - Caroliny Trevisan Teixeira; Vanessa Rizelio; Alexandre Robles; Levi Coelho Maia Barros; Gisele Sampaio Silva; João Brainer Clares de Andrade (Arquivos de Neuro-Psiquiatria)
Background Atrial fibrillation (AF) is a risk factor for cerebral ischemia. Identifying the presence of AF, especially in paroxysmal cases, may take time and lacks clear support in the literature regarding the optimal investigative approach; in resource-limited settings, identifying a higher-risk group for AF can assist in planning further investigation.